Past and future trends of vehicle emissions in Tianjin, China, from 2000 to 2030. (15th July 2019) - Sun, Shida; Zhao, Gang; Wang, Ting; Jin, Jiaxin; Wang, Peng; Lin, Yingchao; Li, Haobo; Ying, Qi; Mao, Hongjun
Abstract: The rapid growth of the vehicle population was regarded as an important factor that contributed to the urban air pollution in China during the past decades. We used Tianjin, a typical megacity facing vehicle pollution problems, as the study domain to investigate a comprehensive estimation of vehicle emissions, including carbon monoxide (CO), volatile organic compounds (VOCs), nitrogen oxides (NOx ), inhalable particles (PM10 ), carbon dioxide (CO2 ) and sulphur dioxide (SO2 ), from 2000 to 2030. The Computer Programme to calculate Emissions from Road Transport (COPERT) model was used to simulate the vehicle emission factors. Historical simulations show that the total emissions of CO, VOCs, NOx, PM10, CO2, and SO2 changed from 545.1 Gg, 70.04 Gg, 60.19 Gg, 6.57 Gg, 6.82 Tg and 12.88 Gg to 259.11 Gg, 34.01 Gg, 55.14 Gg, 3.42 Gg, 25.30 Tg and 0.16 Gg from 2000 to 2016, respectively. Passenger cars (PC) and light-duty vehicles (LDV) were the main contributors to the CO and VOCs emissions. Heavy-duty trucks (HDT) and buses (BUS) were the important contributors to NOx and PM10 . PC was the major contributor to CO2 and SO2 . With respect to the future, four Single Control Policy Scenarios (SCPS), including Passenger car Population Regulation (PPR), Emission Standard Updating (ESU), Public Transportation Promotion (PTP) and Electric Vehicle Popularity (EVP), and Integrated Scenarios (IS), were assembled to describe the impact of future policies on vehicle pollution from 2017 to 2030. Among all SCPS, the results show that the ESU is the more effective policy to control emissions of CO, NOx and PM10, while PPR is the more effective way to reduce emissions of VOCs, CO2, and SO2 . Highlights: A comprehensive estimation of vehicle emissions was investigated in Tianjin from 2000 to 2030. The estimation incorporated the impacts of vehicle emission control policies that were newly implemented. The compositions of vehicular emission standards were considered to improve the accuracy of the estimation. The reduction effects on six pollutants were evaluated under five vehicle emission reduction scenarios.